Multidrug resistance of isolated microorganisms in occluded bile duct stents* - Ali E. DEMİRBAĞ and Aslı KARADEMİR and Erkan PARLAK and Süha ŞEN and Mehmet KARAHAN and Cüneyt KAYAALP and Burhan ŞAHİN (Turkish Journal of Gastroenterology, 2019)
-